EFEKTIVITAS METODE AKTIVITAS ANTIOKSIDAN PADA FRAKSI KECAP MANIS DAN MODEL GLUKOSA-GLISIN-SISTEIN (Jurnal Teknologi Pangan, 2013)
The  oxidative  browning  is  considered  to  have  a  contribute  to  the  flavor, antioxidative activity and color of food. As a result of this Maillard reaction, a variety of by  products,  intermediates  and  brown  pigmens  (melanoidins)   are  produced.  The objectives  of  this  research  was  to  study  the  effect  of  antioxidant  activity  method determination on model and soysauce. The soy  sauce were prepared from sucrose or  coconut  sugar    and  moromi.  The  soysauce  and  model  were  fractionated  by  ultrafiltration in a molecular weight ranging between 10 kDa to 100 kDa. In this study, we  report  that  fractions  of  soysauce.  and  model  have  the  ability  to  scavenging  more strongly DPPH  radical on the fraction with molecular weight of 30 kDa  than 100 kDa,  whereas   the  inhibition  of  oil  oxidation    was  stronger  in  the  fraction  with  molecular  weight <10 kDa to 30 kDa and its activity is more greater than BHT 200 ppm,  although the effect of antioxidants in  soy sauce is greater than the model. Each  fraction of soy sauce  and  a  model  had  a  specific  effect  on  the  inhibition   method  of  oil  oxidation    or sscavenging of  free radicals